GINS motion reveals replication fork progression is remarkably uniform throughout the yeast genome - Matthew D Sekedat; David Fenyö; Richard S Rogers; Alan J Tackett; John D Aitchison; Brian T Chait (Molecular Systems Biology)
Abstract Previous studies have led to a picture wherein the replication of DNA progresses at variable rates over different parts of the budding yeast genome. These prior experiments, focused on production of nascent DNA, have been interpreted to imply that the dynamics of replication fork progression are strongly affected by local chromatin structure/architecture, and by interaction with machineries controlling transcription, repair and epigenetic maintenance. Here, we adopted a complementary approach for assaying replication dynamics using whole genome time‐resolved chromatin immunoprecipitation combined with microarray analysis of the GINS complex, an integral member of the replication fork. Surprisingly, our data show that this complex progresses at highly uniform rates regardless of genomic location, revealing that replication fork dynamics in yeast is simpler and more uniform than previously envisaged. In addition, we show how the synergistic use of experiment and modeling leads to novel biological insights. In particular, a parsimonious model allowed us to accurately simulate fork movement throughout the genome and also revealed a subtle phenomenon, which we interpret as arising from low‐frequency fork arrest.